INTEGRITAS PENGELOLA PDAM TIRTA KARIMUN TAHUN 2018-2020 - Ninda Oktaresa; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Integrity is the cornerstone of good governance. This is a prerequisite for the legitimacy of government activities and more generally for trust in government. This study discusses the Integrity of PDAM Tirta Karimun Management in 2018-2020. The purpose of this research is to determine the integrity in managing PDAM Tirta Karimun Tanjungbatu Branch. Then to find out the settlement process in the Crimes contained in PDAM Tirta Karimun. The theory used in this research is the theory of integrity according to Henry Cloud. This study uses qualitative methods with data collection techniques are interview techniques, documentation and library studies. For data sources on integrity in PDAM management in Tirta Karimun Tanjungbatu branch using a descriptive qualitative research approach. The results of the study explain that the integrity of the management of PDAM Tirta Karimun in 2018-2020 is not optimal, it can be seen based on several indicators of problems, namely the work environment, administrative system, individual behavior, prevention of corruption, with problems in the integrity of managers in PDAM and solving cases of corruption problems. in the PDAM. The inhibiting factor in the integrity of the PDAM Tirta Karimun manager is the lack of attention from the government in preventing cases of corruption problems and preventing the lack of water management in the PDAM. Keywords: Integrity, PDAM.